Comparing pushover methods for irregular high-rise structures, partially infilled with masonry panels. (December 2020) - Rooshenas, Arash
Abstract: Dynamic analysis is the best and most accurate type of analysis for accurate evaluation of structures. However, being time consuming and the need for experience in reviewing the results of this type of analysis, lead engineers to use traditional or adaptive pushover analyzes. In this study, after a comprehensive literature review, three existing irregular high-rise concrete structures with 15-, 20- and 25-story are modeled in 3D and the results of different traditional and adaptive pushover analyzes are compared with the more accurate results of nonlinear dynamic analysis. Also, in performing the analysis, not only the effects of the existence of masonry infill panels, but also the effects of higher modes on the structure have been investigated, simultaneously. Also, by averaging the amount of target displacement, the effect of the lateral loading pattern on the structure has been investigated. Finally, using the SLaMA method, the contribution of concrete frames and masonry infills in the bearing of forces on the structure has been calculated. Reviewing of the results shows that in performing pushover analysis, higher modes, affect the results of adaptive methods and their effects should be considered in the analysis. Also, the results of the SLaMA Method show that in high-rise structures, infill panels have different behavior in withstanding the forces acting on the structure, which should be considered in the analysis of these members.